The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4103/jehp.jehp_59_17
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about rational use of medicines among fresh bachelor of medicine and bachelor of surgery graduates

Abstract: CONTEXT:Fresh Bachelor of Medicine and Bachelor of Surgery graduates (FMGs) are responsible for the majority of prescription errors and irrational use of medicines. Little research has explored their knowledge on rational prescribing practices.AIMS:The present study aimed to evaluate the awareness of rational use of medicines (RUMs) among the FMGs.SETTINGS AND DESIGN:A multicentric, cross-sectional, and questionnaire-based study was conducted among 308 FMGs during the internship orientation program.SUBJECTS AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…that more than half of the interns supported that pregnant females should not consume any drug and two-third of the interns were confused about deciding the correct dose for pediatric patients. [ 30 ] The students in the current study use information that was learned in the course and can transfer it to other situations faced in other disciplines as reported in other studies. [ 9 10 15 ] This will contribute when repeated more frequently and when it is integrated to other clinical disciplines vertically through the medical curriculum, integrating with and identifiable within relevant horizontal modules.…”
Section: Discussionmentioning
confidence: 99%
“…that more than half of the interns supported that pregnant females should not consume any drug and two-third of the interns were confused about deciding the correct dose for pediatric patients. [ 30 ] The students in the current study use information that was learned in the course and can transfer it to other situations faced in other disciplines as reported in other studies. [ 9 10 15 ] This will contribute when repeated more frequently and when it is integrated to other clinical disciplines vertically through the medical curriculum, integrating with and identifiable within relevant horizontal modules.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there were still 29.1 % of nursing students who ignored it. However, a previous study reported that a third of Fresh Bachelor of Medicine and Bachelor of Surgery graduates (FMGs) did not know the same general quality as branded drugs, and they considered them inferior to branded drugs (Chaudhari et al, 2017) Various brands for the same pharmaceutical product are available, leading to further confusion among users. Generic drugs are medicine manufactured by a factor other than an original innovator company that holds patents for certain pharmaceutical products.…”
Section: Discussionmentioning
confidence: 99%
“…Generic drugs are equally efficacious as branded drugs. Thus, the drug regulatory body suppresses receptors to prescribe generic drugs (Chaudhari et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies generally focus on the awareness and knowledge levels of healthcare workers and consumers. In many studies conducted with health-care professionals and health-care students, the level of knowledge about RUM is low [9], [10], [11], [12]. Most of the studies in Turkey show that the consumer knowledge level on RUM is low [13], [14].…”
Section: Introductionmentioning
confidence: 99%